The impact of motivation and training on civil servants' work performance - Idris, Zainal Yahya; Mappatompo, Andi; Purnomo, Joko (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2021)
This study's objectives were: (1) to determine and analyze the influence of motivation on employee performance at the BPBD South Sulawesi Province Office. (2) to determine and analyze the variables that have a dominant effect on the BPBD south Sulawesi province Office employees' performance. This research was conducted at the BPBD office of South Sulawesi Province, with a population and sample of all employees totaling 42 people. The data analysis used was descriptive and multiple linear regression analysis. The study results prove that the performance of employees at the South Sulawesi Provincial BPBD Office is influenced by training. This means that the independent variables studied simultaneously affect improving performance; this shows that employees as human resources need opportunities to develop themselves through increased training to higher levels, impacting the South Sulawesi Provincial BPBD Office's work performance